Growth rate-dependent regulation of 6-phosphogluconate dehydrogenase level in Escherichia coli K-12: beta-galactosidase expression in gnd-lac operon fusion strains. - Baker, H V (1983)
The level of 6-phosphogluconate dehydrogenase is positively correlated with the cellular growth rate. To determine whether growth rate-dependent regulation of expression of gnd, which encodes this enzyme, is carried out by a transcriptional mechanism, the structural genes of the lactose operon were fused to and brought under the control of the gnd promoter through the use of phage Mu d1(Apr lac). Four independent gnd::Mu d1(Apr lac) operon fusion strains were isolated. After the Mu d1 prophage was replaced with lambda p1(209), Lac+ specialized transducing phages carrying the gnd-lac fusions were prepared. These phages were used to demonstrate that the lac genes were fused to the gnd promoter by crossing them with gnd promoter deletion mutants and with polar phage Mu cts-induced gnd mutants. A genetic map of the fusion joints was deduced. The level of beta-galactosidase in each fusion strain was the same in cells growing on acetate as in cells growing on glucose (with specific growth rate constants of 0.1 and 0.55 h-1, respectively) and was unaffected by the presence of a gnd+ gene in trans. Our results suggest that a post-transcriptional mechanism mediates growth rate-dependent regulation of gnd and that this regulation is not autogenous. Models for regulation are discussed with respect to these results and the physiology and DNA sequence of gnd.